A pedagogia libertadora das Parábolas de Jesus: uma leitura à luz do método freireano - Silva, Darci Donizetti da (2006)
The research content has been build upon the reading of the Freirean method, with particular attention to the pedagogy of freedom of Jesus parables. Given the nature of the study, an understanding of Paulo Freire as pedagogue, his life, his historical immersion and the emersion of his method as a transfigured of na oppresive and marginal reality is necessary. Base don Freire pedagogical thoughts we established categories built into three distinctive axis, as follow: Human being as subject of history, a people that immerge in their reality and from it emerge as a free being, able to put into practice their ability to consciously create, not by oppression, but by dialogue generated from proclamation, freedom and denounce. A second moment in the study is related to the historical Jesus. At this point, the evolution of the researches about the person of Jesus, the context in which the parables are born and the parables method itself are dealt with. This approach helps to demonstrate the interrelationship among themes as well as their importance and contributions to each other. A reading that crosses two pedagogies Freire and Jesus are developed. They are made up through the readings of three parables that reflect certain perspectives, such as: the religious one characterized by conflict and questioning the idea of human value as the are given; the social one, throug the expectations presents in human relationships such as convenience, respect and care for one another; the economics one by which human being strives their survival It forces making to moves on beyond their inertia. Parables in this case work as codified situation of a given reality that are introduced to listeners-students. They gather in cultural circles where confront with reality can be realized. In doing so, participants critically reflect in the situation they are immersed, thus reaching out freedom from impriosoning bondages, creating conditions where they can say their own word